Selected Control Strategies of Redundant Marine Equipment - Albrecht, A.; Muc, A.; Szeleziński, A. (Scientific Journal of Gdynia Maritime University, 2017)
This paper presents selected control strategies of redundant devices implicted in one program so that there is a possibility to change the operating mode depending on situation. The problem was evolved on pumps example becaue of their often use both in marine, and shore environment. Simulation model was based on two parallel pumps working in one system. First and second control mode assumes one of the pump working as ‘Master’ and second as ‘Stand-by’. It gives freedom in selection which pump is ‘Master’ and opportunity to change the choice. Third mode comprehends rotating work of two pumps depending on medium pressure value in the system. The control was implemented by using Programmable Logic Controller (PLC) and Human Machine Interface (HMI). Described strategies were checked and simulated in a few different configurations. The aim was to present several complementary solutions to achieve efficient and optimum use of the devices.